Avaliação do kit TF-Test para o diagnóstico das infecções por parasitas gastrintestinais em ovinos - Lumina, Giuliano [UNESP]; Bricarello, Patrizia Ana [UNESP]; Gomes, Jancarlo Ferreira; do Amarante, Alessandro Francisco Talamini [UNESP] (My University, 2006)
This study was performed to standardize parasite egg counting in feces of sheep by TF-Test, in addition to compare this test to the Gordon & Whitlock technique (G&W). Twenty-four lambs were artificially infected with Haemonchus contortus throughout 12 weeks. At the end of this time, faecal samples were taken and animals were slaughtered for worm identification and counting. G&W and TF-Test methods were carried out on each fecal sample. Both tests showed Haemonchus eggs in 95.8% of the samples (P>0.05). The correlation coefficients (r) between fecal egg counts (FEC) using G&W × Total Worm Count (TWC) were r=0.52 (not transformed data) and r=0.85 (transformed data); between FEC by TF-Test × TWC were r=0.51 (not transformed data) and r=0.87 (transformed data). Other 100 fecal samples were taken from naturally infected sheep. In these animals, the G&W and TF-Test methods showed 85% and 86% of fecal samples positive for Strongylidea eggs, respectively (P>0.05). Also in those animals, Eimeria oocysts were found in 33% of fecal samples by TF-Test, whereas in the G&W only 12% were positive (P<0.001). For Strongyloides spp., TF-Test showed 15% of positive fecal samples, whereas G&W showed 5% (P<0.05). In conclusion, both methods were efficient to diagnose gastrointestinal nematodes and TF-Test was superior to diagnose oocysts of Eimeria spp. and eggs of Strongyloides spp; conversely, Strongylidea eggs counting using TF-Test was underestimated.
The evaluation of TF-Test kit for diagnosis of gastrointestinal parasite infections in sheep
Keywords: Diagnostic; FEC; Haemonchus contortus sheep; TF-Test; Animalia; Eimeria; Haemonchus; Haemonchus contortus; Nematoda; Ovis aries; Strongyloides